(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Flexible rubble mound breakwaters are most common structures provided for protection of coastal areas and to achieve tranquil conditions in the harbours against the destructive forces of waves. Design of flexible rubble mound structures is complex as it involves various aspects such as wave-structure interaction, interlocking characteristics of armour, friction between armour and secondary layer etc. A major aspect in the design of rubble mound structures is the optimum weight of the armour units required to withstand the design waves. It is a universal practice to finalize the section of breakwater based on hydraulic model tests in wave flumes wave basins to confirm the conceptual design evolved using empirical formulae. Some of the new concepts have been introduced by CWPRS for optimal design of rubblemound breakwaters.